Postharvest Disease Control of Vanilla (vanilla planifolia andrews) by Control Atmosphere. - Toelddjo Martoredjo; Bambang Hadisutrisno; Abdul Choliq (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1981)
-